COHERENT ADDITION OF THE SCATTERED AND DIFFRACTED FIELDS IN PROBLEMS OF LIGHT SCATTERING BY LARGE CRYSTALS - Popov A.A. (My University, 1988)
The problem of correct addition of diffracted and scattered fields generally arises in problems of light scattering by large crystals. It is of particular importance in the case of crystals with plane-parallel faces (hexagonal plates, hexagonal columns and the like), because their diffracted and scattered fields are comparable in magnitude. We proposed the 'beam' computation method based on geometric optics. It involves an algorithmic 'assembly' of rays propagating in parallel after emergence from the crystal, into several beams, each of which is part of the front of a homogeneous or inhomogeneous plane wave. The application of this method to the determination of the far-zone light field scattered from a crystal allows one to use the same formal approach as in the case of the diffracted field. It thus becomes possible to add the diffracted and scattered fields with correction for phase differences, i.e., to perform coherent addition.